Heart Failure With Midrange Ejection Fraction: Prior Left Ventricular Ejection Fraction and Prognosis - Zhang, Xinxin; Sun, Yuxi; Zhang, Yanli; Chen, Feifei; Zhang, Shuyuan; He, Hongyan; Song, Shuang; Tse, Gary; Liu, Ying (Frontiers in Cardiovascular Medicine, 2021)
Aims: Evidence-based guidelines for heart failure management depend mainly on current left ventricular ejection fraction (LVEF). However, fewer studies have examined the impact of prior LVEF. Patients may enter the heart failure with midrange ejection fraction (HFmrEF) category when heart failure with preserved ejection fraction (HFpEF) deteriorates or heart failure with reduced ejection fraction (HFrEF) improves. In this study, we examined the association between change in LVEF and adverse outcomes. Methods: HFmrEF patients with at least two or more echocardiograms three months apart at The First Affiliated Hospital of Dalian Medical University between 1st September 2015 and 30th November 2019 were identified. According to the prior LVEF, the subjects were divided into improved group (prior LVEF <40%), stable group (prior LVEF between 40%-50%), and deteriorated group (prior LVEF≥50%). The primary outcomes were cardiovascular death, all-cause mortality, hospitalization for worsening heart failure and composite event of all-cause mortality or all-cause hospitalization. Results: A total of 1168 HFmrEF patients (67.04% male, mean age 63.60±12.18 years) were included. The percentages of improved, stable, and deteriorated group were 310 (26.54%), 334 (28.60%) and 524 (44.86%), respectively. After a period of follow-up, 208 patients (17.81%) died and 500 patients met the composite endpoint. The rates of all-cause mortality were 35 (11.29%), 55 (16.47%), 118 (22.52%) and the composite outcome were 102 (32.90%), 145 (43.41%) and 253 (48.28%) for the improved, stable and deteriorated groups, respectively. Cox regression analysis showed that the deterioration group had higher risk of cardiovascular death (HR: 1.707, 95% CI: 1.064-2.739, P=0.027), all-cause death (HR 1.948, 95%CI 1.335-2.840, P=0.001), and composite outcome (HR 1.379, 95% CI, 1.096-1.736, P=0.006) compared to the improvement group. The association still remained significant after fully adjusted for both all-cause mortality (HR=1.899, 95%CI 1.247-2.893, P=0.003) and composite outcome (HR: 1.324, 95% CI: 1.020-1.718, P=0.035). Conclusion: HFmrEF patients are heterogeneous with three different subsets identified, each with different outcomes. Strategies for managing HFmrEF should include previously measured LVEF to allow stratification based on direction changes in LVEF to better optimize treatment. Key Words：heart failure, mid-range ejection fraction, prior, left ventricular ejection fraction, prognosis.